Pemberian Pendidikan Kesehatan dengan CERDIK menggunakan Media Slide Power Point dan Leaflet tentang Pencegahan Hipertensi - Apri Nur Wulandari (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background: Noncommunicable diseases (NCDs) are the leading cause of death, accounting for 73% of all deaths globally. It is expected that the increase in NCD fatalities will continue as a result of detrimental changes in human and environmental behavior. Hypertension is a highly prevalent NCD condition. One thing that may be done to prevent NCDs is to provide relevant information about disease prevention and control. CERDIK can be used to provide information in the form of health education. Media is required for health education so that information can be delivered and accepted well by participants. Purpose:  The purpose of this community service is to increase the knowledge of the elderly using leaflets on preventing hypertension with CERDIK. Methods: This community service was carried out by providing health education in the Sukorame Region, Bantul, on October 26, 2022. The target community members who attended were old adults and the elderly, totaling 52 people. Providing health education is carried out using the lecture method with the help of PowerPoint slides and media leaflets about preventing hypertension with CERDIK. Results: The average knowledge of the target community about preventing hypertension after being given health education was 86.5%; this was included in the category of good knowledge (76%–100%). Conclusion: By increasing the knowledge of the elderly about hypertension prevention using the CERDIK method, it is hoped that it can empower the elderly to be able to detect and control the hypertension they experience early.